CW fiber laser for second harmonic generation - Novak, Vid (Strojniški vestnik, 2011)
We report on a reduced-complexity laser-diode-seeded master-oscillator-power-amplifier setup of a continuous wave fiber laser, with a single-stage ytterbium doped photonic crystal fiber amplifier. The laser is capable of generating up to 7.5 W single-transverse-mode, narrow-linewidth, polarized output suitable for second harmonic generation. The approach used possesses a further power scaling potential.
Keywords: iterbijevi vlakenski ojačevalniki; laser s frekvenčno podvojenim izhodom; laser s polariziranim izhodom; laser s transverzalno-enorodovnim izhodom; laser tipa oscilator-ojačevalnik; laser z ozkopasovnim izhodom; laserji; MOPA; narrow-linewidth; polarized output; second harmonic generation; single mode; Yb fiber amplifier